Loss‐of‐function mutations in melanocortin-1 receptor modulate immune response in teleost fishes. Issue 131 (December 2022) - Fierro-Castro, Camino; Rotllant, Josep; Cerdá-Reverter, Jose Miguel; Tort, Lluís
Abstract: The melanocortin system is an ancient neuroendocrine system conserved from teleosts to mammals. The melanocortin system is a set of complex neuroendocrine signaling pathways involved in numerous physiological processes, and particularly associated with the hypothalamic-pituitary-interrenal (HPI) axis response. The melanocortin 1 receptor (MC1R) is the central melanocortin receptor involved in pigmentation in vertebrates, including fish. In order to assess the immune role of MC1R, this study used a homozygous Mc1r knockout zebrafish. Hence, skin cortisol levels, variations in the blood leucocyte population, as well as the expression levels of immune genes in various tissues of wild-type TU strain (Tübingen, Nüsslein-Volhard Lab) (WT) and homozygous mc1r knockout zebrafish ( mc1r K.O. ) stimulated with LPS was carried out. Results show that the mc1r K.O. mutant fish produce lower levels of cortisol in mucus and fewer macrophages in blood after exposure to LPS compared to control fish. Regarding the expression of immune genes, mutant fish show a significant increase in the expression of the anti-inflammatory interleukin il10 . These results suggest that the mc1r K.O. mutant fish may follow an alternative mechanism among the immune responses, where macrophages seem to have an anti-inflammatory function, attenuating nitric oxide (NO) production and providing an advantage through the mitigation of excessive or strong inflammatory reactions. Nonetheless, a lower number of this cell type could imply a reduced phagocytic potential in the face of an infection. At the same time, lower cortisol levels in the mc1r K.O. mutant fish could be an advantage as for the lower susceptibility to stress and the physiological and metabolic consequences of high cortisol levels. Graphical abstract: Image 1 Highlights: Inactivating mutations of mc1r gene impair steroidogenesis in zebrafish. Inflammatory response is differentially regulated in mc1r K.O. after LPS challenges. mc1r K.O. zebrafish show depressed phagocytic potential. mc1r K.O. zebrafish exhibit alternative pathway of macrophage activation.